SISTEM PENDUKUNG KEPUTUSAN PENENTUAN KELAYAKAN PEMBERIAN KREDIT PADA NASABAH MENGGUNAKAN METODE SIMPLE ADDITIVE WEIGHTING (SAW) PADA BANK BTPN SYARIAH CABANG JAMBI: Decision Support System;BTPN;Mysql;Website. - Adriana, Windy; Mardianti, Anggi (FORTECH (Journal of Information Technology), 2022)
BTPN Syariah Jambi is a company engaged in financial services. Problems ingranting credit to debtors by the bank do not always go according to plan, so thatin carrying out its operations, banks must be more careful so that banks do not experience defaults which result in bad loans. The purpose of research on lendingon a customer-based website. The method used in this research is Simple Addtive Weighting (SAW). Based on the results of the research, with the existence of asupport system that is in accordance with the provision of credit to customers using the Simple Addtive Weighting method to minimize errors caused by humanerror, the program produces a ranking graph, which makes it easier to see the rankings.